Establishing pathological cut-offs for lateral ventricular volume expansion rates - Dwyer, Michael G; Hagemeier, Jesper; Bergsland, Niels; Horakova, Dana; Korn, Jonathan R; Khan, Nasreen; Uher, Tomas; Medin, Jennie; Silva, Diego; Vaneckova, Manuela; Havrdova, Eva Kubala; Zivadinov, Robert (NeuroImage. Clinical, 2018)
BACKGROUND: A percent brain volume change (PBVC) cut-off of -0.4% per year has been proposed to distinguish between pathological and physiological changes in multiple sclerosis (MS). Unfortunately, standardized PBVC measurement is not always feasible on scans acquired outside research studies or academic centers. Percent lateral ventricular volume change (PLVVC) is a strong surrogate measure of PBVC, and may be more feasible for atrophy assessment on real-world scans. However, the PLVVC rate corresponding to the established PBVC cut-off of -0.4% is unknown. OBJECTIVE: To establish a pathological PLVVC expansion rate cut-off analogous to -0.4% PBVC. METHODS: We used three complementary approaches. First, the original follow-up-length-weighted receiver operating characteristic (ROC) analysis method establishing whole brain atrophy rates was adapted to a longitudinal ventricular atrophy dataset of 177 relapsing-remitting MS (RRMS) patients and 48 healthy controls. Second, in the same dataset, SIENA PBVCs were used with non-linear regression to directly predict the PLVVC value corresponding to -0.4% PBVC. Third, in an unstandardized, real world dataset of 590 RRMS patients from 33 centers, the cut-off maximizing correspondence to PBVC was found. Finally, correspondences to clinical outcomes were evaluated in both datasets. RESULTS: ROC analysis suggested a cut-off of 3.09% (AUC = 0.83, p < 0.001). Non-linear regression R2 was 0.71 (p < 0.001) and a - 0.4% PBVC corresponded to a PLVVC of 3.51%. A peak in accuracy in the real-world dataset was found at a 3.51% PLVVC cut-off. Accuracy of a 3.5% cut-off in predicting clinical progression was 0.62 (compared to 0.68 for PBVC). CONCLUSIONS: Ventricular expansion of between 3.09% and 3.51% on T2-FLAIR corresponds to the pathological whole brain atrophy rate of 0.4% for RRMS. A conservative cut-off of 3.5% performs comparably to PBVC for clinical outcomes.
Keywords: dospělí; Databases, Factual; relabující-remitující roztroušená skleróza; Magnetic Resonance Imaging; Humans; databáze faktografické; Image Processing, Computer-Assisted; lidé středního věku; Middle Aged; magnetická rezonanční tomografie; Lateral Ventricles; mužské pohlaví; ventriculi laterales; Nonlinear Dynamics; Severity of Illness Index; stupeň závažnosti nemoci; ROC Curve; referenční hodnoty; Adult; Multiple Sclerosis, Relapsing-Remitting; Disease Progression; počítačové zpracování obrazu; nelineární dynamika; Ventricular volume; ženské pohlaví; ROC křivka; lidé; Disability Evaluation; Multiple sclerosis; Reference Values; Male; progrese nemoci; NEDA; Brain atrophy; Pathological cutoff; posuzování pracovní neschopnosti; Female